Prevalence Of Transfusion Transmitted Infection Markers and Geographic Mapping to Identify Safe Areas for Holding Blood Donation Camps in Surat City - Shukla, Rinku V; Patel, Gulab R; Shah, Avani P; Gupte, Snehalata C (National Journal of Community Medicine, 2013)
Background: Our Regional Blood Transfusion Centre collects about 35000 blood units annually and supplies about 50000 units to about 500 hospitals and Nursing homes. Aims: To assess variation in HBV, (HCV), human (HIV 1and 2, and syphilis infection rates in voluntary donors from different areas in Surat city and to identify trends of transfusion transmitted infections over the period of time. Methods: This study presents data of 241915 blood units collected in 3588 camps from 2001 to 2010. In Surat city, 218497 blood units were collected in 3219 camps. The samples were screened for tests like HIV1+2, HCV, hepatitis B surface antigen (HBsAg), and VDRL. The city was divided in nine groups each having an average area of 33.24 sq. km. The prevalence of transfusion transmitted infections (TTI) among blood donors in these areas has been estimated. Results: Camp blood collection increased from 99523 in 2001-05 to 142392 in 2006-10. The average rate of TTI in Surat was 0.24% HIV, 0.96% HBsAg, 0.17% HCV and 0.15% VDRL. HIV prevalence declined from 0.38% to 0.14%, HBsAg 1.17% to 0.83%, HCV 0.31 to 0.07% and VDRL from 0.23% to 0.09% in 2006-10 compared to 2001-05. Areas of group 1 have maximum seropositivity for HBsAg and VDRL with group 7, 8 and 9 having seropositivity more for HIV and HCV. Conclusion: Study highlights the safe areas of collecting blood in group 5, 6 and 7. Group 1, 8 and 9 have high prevalence areas of TTI which should be avoided for holding blood donation camps.